Deploying and managing Hyper-V LiveLessons - Posey, Brien; Safari eBooks ([Place of publication not identified] : Sams, 2015)
"Hyper-V in Windows Server 2012 R2 enables admins to create a virtualized server computing environment that is designed to improve the efficiency of your computing resources by utilizing more of your hardware resources. This is possible through the use of Hyper-V to create and manage virtual machines and their resources. Each virtual machine is a virtualized computer system that operates in an isolated execution environment, allowing multiple operating systems to simultaneously run on one physical computer. This video is designed to teach virtualization administrators how to use Hyper-V and System Center Virtual Machine Manager. The video starts at the very beginning by covering basic tasks, such as manually creating virtual machines. From there concepts and foundational guidance are presented in an intuitive manner, as renowned author Brien Posey dives into more advanced topics such as storage planning, network bandwidth utilization, and automated virtual machine creation."--Resource description page.
Title from resource description page (viewed July 20, 2015).
Presenter, Brien Posey.
Keywords: Microsoft Windows server Hyper-V.; Virtual computer systems; Electronic books